The incidence and factors predicting survival among preterm infants with respiratory distress syndrome admitted to neonatal intensive care unit - Naphaklacha Pholanun; Boonjai Srisatidnarakul; Joy Longo (Universitas Airlangga, 2022)
Introduction: Respiratory distress syndrome (RDS) or hyaline membrane disease (HMD) is the most common cause of neonatal morbidity and mortality in preterm infants. The aims of the study were to determine the incidence of RDS in preterm infants in Thailand and to identify factors predicting survival of preterm infants with RDS. Methods: A retrospective cohort study was conducted with 820 preterm infants from January 2016 to December 2019 in the NICUs of a tertiary hospital located in the north of Thailand. Data were collected from hospital medical records. The incidence of RDS was analyzed. Binary logistic regression was used to predict factors related to survival of preterm infants with RDS. Results: The incidence of RDS in infants born at <37 weeks gestation was 44.15% of all preterm infants. Moreover, birth weight and length of stay could significantly predict survival of preterm infants with RDS (p<.05). Conclusions: RDS was frequent in preterm infants <37 weeks gestation. The findings of this study can increase factors contributing to RDS in preterm infants that appropriate care can initiated to improve survival of preterm infants with RDS.